The present study was conducted on ten each uropygial glands of 6 to 8 months old healthy Kadaknath and White Leghorn breeds of poultry. The tissue samples were stained by H & E for normal histological structures, Verhoeff’s stain for collagen and elastic - Kanasiya, S; Karmore, SK; Deshmukh, SK; Bahariya, RK; Gupta, SK (Indian Journal of Veterinary Sciences and Biotechnology, 2017)
The present study was conducted on ten each uropygial glands of 6 to 8 months old healthy Kadaknath and White Leghorn breeds of poultry. The tissue samples were stained by H & E for normal histological structures, Verhoeff’s stain for collagen and elastic fibers, PAS (Periodic Acid Schiff’s) for glycogen and Alcian Blue PAS method for acid mucopolysaccharides. The uropygial gland in Kadaknath and White Leghorn was composed of two lobes. Each lobe had a single duct and these ducts were joined together by isthmus. The thickness of capsule was more in White Leghorn than Kadaknath breed. The lumen of tubules showed higher concentration of secretary product in Kadaknath breed. Numbers of tubules were higher in Kadaknath. No aggregation of lymphocytes was found in the preen gland of White Leghorn, whereas in Kadaknath, there was large number of lymphocytes aggregation alongwith lymphatic nodules. Melanin pigmentation was the characteristic feature of Kadaknath which was found towards the central cavity and in between ductules. The capsule of White Leghorn showed intense PAS activity, while moderate activity was found in Kadaknath breed of poultry. Intense ACPase reaction was noticed in capsule of uropygial gland of Kadaknath and White Leghorn breeds of poultry.
Keywords: Kadaknath; White Leghorn; Histochemistry; Histology; Uropygial gland